Vazio existencial contemporâneo: diálogo epistemológico entre logos e mythos na psicologia - Alencar, Kenia Cristiana de Lima (2024)
Existential vacuum is a very common experience in the contemporary zeitgeist. This experience has been continually associated with the experiential situation of postmodern man who, steeped in the philosophy of dataism and pragmatism, and distanced from his mythos, has experienced feelings of being one of life’s misfits. The aim of the theoretical study described herein was to understand the relationship between contemporary psychic suffering and the crisis of existential meaning, and the possible epistemological implications in terms of a possible dialogue between logos and mythos in psychology. The dissertation is presented in the form of five articles, preceded by an introduction and followed by a final articulation by way of conclusion. The articles correspond successively to the gradual, complementary stages of the study, as follows: a) and b) systematic review of the articles in the literature, in psychology, about the meaning of life and existential vacuum, carried out in two phases: a more generic meta-analysis and the other more specific and in greater depth, focusing on qualitative and theoretical studies, both encompassing the period between 2000 and 2023; c) an integrative review of studies about the meaning of life and existential vacuum, the parameter being articles addressing the phenomenological, existential and humanistic matrix, found in the second stage of the aforementioned systematic review; d) theoretical/ epistemological analysis of two approaches in psychology that describe the Mythos and its role in clinical psychology – the Analytical Psychology of Jung, and the Existential Humanism of Rollo May – and which stemmed from the choice of two case studies/ narratives, Miss Miller and Deborah Blau, found in the works of the aforementioned authors; e) theoretical/conceptual analysis of the philosophy of the neoKantian Ernst Cassirer, describing mythos as scientific language, revealing affinity with the phenomenological approach in psychology. To conclude, an epistemological analysis is addressed in depth by means of a weaving of the content, presenting the implications of the dialogue between Logos and Mythos for the creation of a contemporary understanding in psychology. As a backdrop to this reflection, the phenomenology of Edmund Husserl is adopted, which is sympathetic to the epistemology of Cassirer. The main results achieved in each phase and in the study as a whole were: a) prevalence of the nomothetic impulse and the quantifier in contemporary psychological research into existential issues; b) among the qualitative and/or theoretical studies, predominance of those underpinned by logotherapy, bringing the dimension of meaning and existence to the therapeutic setting; c) emphasis on the meaning of life construct as the core of mental health; d) heterogeneity in the definition of the construct of existential vacuum; f) diversity of theoretical resources (e.g., Socratic dialogue) and empirical resources (e.g., support group) in the management of existential vacuum and meaning of life; g) relevance of philosophical anthropology for an understanding of the epistemological fundaments of the studies developed; h) importance of integrating the mythos into psychology as a way of characterizing subjective experience, of access to the pains of the soul, as a means of signification and as an existential necessity; i) need for characterization of the mythos, as a symbolic form founded on sensitivity and expressivity, tautegorical in nature, beyond the allegoric, for the production of knowledge in psychology and the basis for clinical practice in the area of mental health.